The The Effect of MRD (Milk of Red Rice and Dates) Composition on the Degradation Stability of Milk Dyes and The Content of Milk Microbial Contamination (Universitas Negeri Semarang, 2022)
Milk is a nutritious drink that contains nutrients and vitamins needed by the body. In this study, a variant of the composition of red rice with Sukari dates and tested to obtain the best level of milk stability in the form of MRD. The composition of MRD was varied, namely MRD type I and MRD type II. The method used in this research is the analysis of milk dye degradation, milk stability analysis, microbial contamination analysis, and organoleptic testing. The results of the research on the degradation of milk dyes showed that both types of milk were in 2nd order with the reaction rate constant for type I MRD being 0.0582 and MRD type II was 0.0181. The level of stability of milk from MRD type I is 2nd order with a rate constant of 0.0953 and MRD type II is 1st order with a rate constant of 0.0998. For the microbial contamination assay showed that the microbial contamination test, showed that the two types of MRD, namely MRD type I and MRD type II were still within the safe limits and did not exceed the safe limits required by the SNI 7388:2009. The results of the hedonic test showed that the MRD type II was more favored by the respondents than the MRD type I.